2008
DOI: 10.1007/s11627-008-9152-z
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variation in rye (Secale cereale L.) analyzed using polymorphic and sequenced AFLP markers

Abstract: Amplified fragment length polymorphism (AFLP) analysis of 24 in vitro regenerated rye plants was performed in order to evaluate the somaclonal variation rate in this species and to identify rye genomic regions where mutations are preferentially promoted by in vitro culture processes. Regenerated plants were obtained from cell lines derived from immature embryos and plants were regenerated by somatic embryogenesis. Twenty-three regenerants showed variation when compared against sibling plants obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…These changes can modify the regenerated plant phenotype and thus are considered to be an impediment to processes such as clonal micropropagation or genetic transformation. The rate of somaclonal variation can differ between species and, in some, the mutation frequency is quite high, 50.8% of variable regenerated plants, as previously reported for rye (Linacero and Vázquez 1993) and subsequently confirmed by others (Linacero et al 2000;Rakoczy-Trojanowska 2002;de la Puente et al 2008). Somaclonal variation, considered as a mutation inductive process, shows particular features (Vázquez 2001).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…These changes can modify the regenerated plant phenotype and thus are considered to be an impediment to processes such as clonal micropropagation or genetic transformation. The rate of somaclonal variation can differ between species and, in some, the mutation frequency is quite high, 50.8% of variable regenerated plants, as previously reported for rye (Linacero and Vázquez 1993) and subsequently confirmed by others (Linacero et al 2000;Rakoczy-Trojanowska 2002;de la Puente et al 2008). Somaclonal variation, considered as a mutation inductive process, shows particular features (Vázquez 2001).…”
Section: Introductionsupporting
confidence: 57%
“…Epigenetic regulation is a common cellular mechanism underlying both genetic and epigenetic instabilities in plant tissue cultures (Zhang et al 2009;Vázquez and Linacero 2010). In rye, several methodologies have been used to assess in vitro induced variation (Linacero and Vázquez 1992a, b;Linacero and Vázquez 1993;Puolimatka and Karp 1993;Linacero et al 2000;Rakoczy-Trojanowska 2002;de la Puente et al 2008) confirming high levels of genetic variability in this species. In this study, the ISSR technique was applied for the first time in regenerated rye plants, and a high number of plants with at least one genetic modification were observed.…”
Section: Discussionmentioning
confidence: 99%
“…This does not mean that all tissue-cultured cells contained a particular mutation but indicates that it was present in at least some cells in each callus sample. A similar phenomenon was observed in rye, where variation in the same RAPD or AFLP products was detected in plants regenerated from different initial calli (Linacero et al, 2000;de la Puente et al, 2008). Those authors showed that such independent mutational events affected exactly the same sequences.…”
Section: Discussionsupporting
confidence: 65%
“…Micropropagation techniques are of practical importance; many currently published papers on in vitro-induced genetic changes relate to the variability of cloned plants (somaclonal variation). Most of them show a rich array of genetic variants (Bednarek et al, 2007;Jin et al, 2008;de la Puente et al, 2008;Aversano et al, 2009;Mo et al, 2009) though only a small part of the genetic variability is transferred from cultured tissues to micropropagated plants. Genetic variation in vitro arises from chromosome alterations and/or changes on the DNA level (Lee and Phillips, 1988;Kaeppler et al, 2000;Kwasniewska et al, 2012), but it remains unclear whether these phenomena occur independently.…”
Section: Discussionmentioning
confidence: 99%
“…Such nonrandom genetic changes may result from the occurrence of the regions within U. victoris genome that show increased susceptibility to variation in culture in vitro. Existence of such regions was suggested earlier in Secale cereale (Linacero et al 2000, De la Puente et al 2008, Arabidopsis thaliana (Polanco and Ruiz 2002), Allium sativum (Al-Zahim et al 1999), Iris pseudacorus (Kozyrenko et al 2004), Allium cepa (Bohanec et al 1995) and Eucalyptus globulus (Mo et al 2009). Simultaneous occurrence of the same novel band in several regenerants may also results from their origin from the callus composed of cells bearing specific mutation.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 72%